1993
DOI: 10.1007/bf02382632
|View full text |Cite
|
Sign up to set email alerts
|

Classical genetic markers and DNA markers: A commensal marriage

Abstract: ABSTRACT. In this paper, we present an overview of classical genetic markers in nonhuman primates and then contrast the discriminatory powers of these markers with DNA markers. We have restricted the scope of our discussion to genetic markers found in blood, since they have been studied most extensively over the past 30 years. For example, immunoglobulin allotypes, complement markers, transferrins, and other protein markers can be identified using serum or plasma. Lymphocytes carry the major histocompatibility… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1993
1993
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…Were it sufficient to identify the sires of 99% of all infants and to ensure that the probability that two individuals exhibit the same genotypes at all loci studied is as low as one in one million, then the six loci marked with an asterisk in Table III should suffice. These loci are highly informative and unlinked and could constitute the primary set for most cases, with other loci, even RFLPs and protein coding loci, being employed only when uncertainty persists, a strategy that Stone et al [1993] have termed "progressive paternity exclusion." Since far less certainty is adequate for sound genetic management practices than for human paternity litigation, the three most informative loci should suffice for routine colony management under most circumstances.…”
Section: Genetics Of Individuals and Familiesmentioning
confidence: 99%
“…Were it sufficient to identify the sires of 99% of all infants and to ensure that the probability that two individuals exhibit the same genotypes at all loci studied is as low as one in one million, then the six loci marked with an asterisk in Table III should suffice. These loci are highly informative and unlinked and could constitute the primary set for most cases, with other loci, even RFLPs and protein coding loci, being employed only when uncertainty persists, a strategy that Stone et al [1993] have termed "progressive paternity exclusion." Since far less certainty is adequate for sound genetic management practices than for human paternity litigation, the three most informative loci should suffice for routine colony management under most circumstances.…”
Section: Genetics Of Individuals and Familiesmentioning
confidence: 99%
“…Microsatellite marker maps of the human genome [Dib et al, 1996] and other experimental organisms (such as the chicken, rat, and mouse) are widely available, facilitating linkage analysis in these species, but little research has been conducted to identify microsatellite markers in the rhesus macaque. Most publications report only a small number of microsatellite markers, which are either newly identified for that species or are human markers that have been tested in another primate species [Blanquer & Crouau, 1995;Coote & Bruford, 1996;Domingo et al, 1997;Kayser et al, 1995;Inoue & Takenaka, 1993;Jurka, 1995;Rogers et al, 1995;Stone et al, 1993]. As the position of microsatellite markers is often conserved between closely related mammalian species [Moore et al, 1991], and so many microsatellite markers have already been identified in the human, the testing of human microsatellites for development of marker sets in other nonhuman primate species is a valid approach.…”
Section: Introductionmentioning
confidence: 99%
“…Statistical programmes for scoring banding patterns which take into account genetic factors affecting band inheritance and/or presence of a band on a fingerprint, allow a statistical probability to be assigned to the individuality of each fingerprint (KRAWCZAK & BOCKEL, 1992). Bands not found in either parent may be seen in an infant, following mutation (STONE et al, 1993). Such mutations in minisatellite sequences arise at a significant frequency in germline tissue (0.001 per fragment per gamete), but less so in somatic tissue.…”
Section: Interpretation Of Fingerprint Gelsmentioning
confidence: 99%